Sales Information System At Apotek Aulia Padang With Visual Basic Programming - Yusman, Yanti (Jurnal Sains dan Informatika, 2016)
Have been conducted by research at Apotek Aulia Padang where problems taken as base in writing of this journal that is sale of medicines pursuant to doctor recipe. Presentation of report related to sale information presented in the form of tables which this matter assumed will be more clear and accurate when compared to previous report only made by using form which have made available and without mentioning sold medicines type. Biggest benefit from presentation of this report that is to be can predict to water down in is ready of information related to data sale of the medicine. And in its application scheme, used by visual basic 6.0 programing language with aim to be easier understood by user.